American Association for the Surgery of Trauma–World Society of Emergency Surgery guidelines on diagnosis and management of peripheral vascular injuries. Issue 6 (December 2020) - Kobayashi, Leslie; Coimbra, Raul; Goes, Adenauer M. O.; Reva, Viktor; Santorelli, Jarrett; Moore, Ernest E.; Galante, Joseph; Abu-Zidan, Fikri; Peitzman, Andrew B.; Ordonez, Carlos; Maier, Ronald V.; Di Saverio, Salomone; et al.
Abstract : ABSTRACT: The peripheral arteries and veins of the extremities are among the most commonly injured vessels in both civilian and military vascular trauma. Blunt causes are more frequent than penetrating except during military conflicts and in certain geographic areas. Physical examination and simple bedside investigations of pulse pressures are key in early identification of these injuries. In stable patients with equivocal physical examinations, computed tomography angiograms have become the mainstay of screening and diagnosis. Immediate open surgical repair remains the first-line therapy in most patients. However, advances in endovascular therapies and more widespread availability of this technology have resulted in an increase in the range of injuries and frequency of utilization of minimally invasive treatments for vascular injuries in stable patients. Prevention of and early detection and treatment of compartment syndrome remain essential in the recovery of patients with significant peripheral vascular injuries. The decision to perform amputation in patients with mangled extremities remains difficult with few clear indicators. The American Association for the Surgery of Trauma in conjunction with the World Society of Emergency Surgery seeks to summarize the literature to date and provide guidelines on the presentation, diagnosis, and treatment of peripheral vascular injuries. LEVEL OF EVIDENCE: Review study, level IV.